Rural entrepreneurship capital and firm performance: A youth perspective - Ambara Purusottama (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
This study aims to review the concept of entrepreneurship capital in the context of rural entrepreneurship. Rural entrepreneurship is becoming increasingly popular because it is considered as the proper instrument in stemming urbanization. This research examines the relationship between entrepreneurship and firm performance in the perspective of resource-based theory. The researcher used a structural equation model approach as a tool to measure the relationship. The unit of analysis of this study is a rural youth entrepreneur domiciled in East Java Province, Malang Regency, Bojonegoro, and Tuban. This study used a quantitative approach involving 733 youth entrepreneurs with a purposive sampling technique. The results of the study found that not all elements of entrepreneurship capital were able to influence firm performance. The three elements are cultural capital, social capital, and human capital. Other findings show financial capital is no longer as a major consideration to support entrepreneurship as in previous studies.